Production and characterization of thermostable alkaline protease of Bacillus subtilis (ATCC 6633) from optimized solid‐state fermentation. (15th January 2015) - Chatterjee, Joyee; Giri, Sudipta; Maity, Sujan; Sinha, Ankan; Ranjan, Ashish; Rajshekhar,; Gupta, Suvroma
Abstract Proteases are the most important group of enzymes utilized commercially in various arenas of industries, such as food, detergent, leather, dairy, pharmaceutical, diagnostics, and waste management, accounting for nearly 20% of the world enzyme market. Microorganisms of specially Bacillus genera serve as a vast repository of diverse set of industrially important enzymes and utilized for the large‐scale enzyme production using a fermentation technology. Approximately 30%–40% of the cost of industrial enzymes originates from the cost of the growth medium. This study is attempted to produce protease from Bacillus subtilis (ATCC 6633) after optimization of various process parameters with the aid of solid‐state fermentation using a cheap nutrient source such as wheat bran. B. subtilis (ATCC 6633) produces proteases of molecular weight 36 and 20 kDa, respectively, in the fermented medium as evident from SDS zymogram. Alkaline protease activity has been detected with optimum temperature at 50 °C and is insensitive to ethylenediaminetetraacetic acid. This thermostable alkaline protease exhibits dual pH optimum at 7 and 10 with moderate pH stability at alkaline pH range. It preserves its activity in the presence of detergent such as SDS, Tween 20, and Triton X‐100 and may be considered as an effective additive to detergent formulation with some industrial importance.